NOTCH1 Can Initiate NF-κB Activation via Cytosolic Interactions with Components of the T Cell Signalosome - Shin, Hyun Mu; Tilahun, Mulualem E.; Cho, Ok Hyun; Chandiran, Karthik; Kuksin, Christina Arieta; Keerthivasan, Shilpa; Fauq, Abdul H.; Golde, Todd E.; Miele, Lucio; Thome, Margot; Osborne, Barbara A.; Minter, Lisa M. (Frontiers in Immunology, 2014)
T cell stimulation requires the input and integration of external signals. Signaling through the T cell receptor (TCR) is known to induce formation of the membrane-tethered CBM complex, comprising CARMA1, BCL10 and MALT1, which is required for TCR-mediated NF-kappaB activation. TCR signaling has been shown to activate NOTCH proteins, transmembrane receptors also implicated in NF-kappaB activation. However, the link between TCR-mediated NOTCH signaling and early events leading to induction of NF-kappaB activity remains unclear. In this report, we demonstrate a novel cytosolic function for NOTCH1 and show that it is essential to CBM complex formation. Using a model of skin allograft rejection, we show in vivo that NOTCH1 acts in the same functional pathway as PKCtheta, a T cell-specific kinase important for CBM assembly and classical NF-kappaB activation. We further demonstrate in vitro NOTCH1 associates physically with PKCtheta and CARMA1 in the cytosol. Unexpectedly, when NOTCH1 expression was abrogated using RNAi approaches, interactions between CARMA1, BCL10 and MALT1 were lost. This failure in CBM assembly reduced IkappaBalpha phosphorylation and diminished NF-kappaB-DNA binding. Finally, using a luciferase gene reporter assay, we show the intracellular domain of NOTCH1 can initiate robust NF-kappaB activity in stimulated T cells, even when NOTCH1 is excluded from the nucleus through modifications that restrict it to the cytoplasm or hold it tethered to the membrane. Collectively, these observations provide evidence that NOTCH1 may facilitate early events during T cell activation by nucleating the CBM complex and initiating NF-kappaB signaling.